Enhancement of immune responses by co-stimulation of TLR3 - TLR7 agonists as a potential therapeutics against rabies in mouse model. (August 2021) - Farahtaj, Firouzeh; Gholami, Alireza; Khosravy, Mohammad Sadeq; Gharibzadeh, Safoora; Niknam, Hamid Mahmoudzadeh; Ghaemi, Amir
Abstract: Rabies is always fatal, when post-exposure prophylaxis is administered after the onset of clinical symptoms. To date, there is no effective treatment of rabies once clinical symptoms has initiated. Therefore, we aimed to provide evidences which indicate the promising effects of combination treatment with TLR agonists following rabies infection. Four groups of rabies infected-mice (10-mice/group) were treated with PolyI:C 50 μg (a TLR3 agonist), Imiquimod50 μg (a TLR7 agonist), (Poly + Imi)25 μg and (Poly + Imi)50 μg respectively. The immune responses in each experimental groups were investigated in the brain through evaluation of GFAP, MAP2, CD4, HSP70, TLR3, TLR7 and apoptotic cell expression as well as determination of IFN-γ, TNF-α and IL-4, levels. The treatment with combination of agonists (Poly + Imi)50 μg/mouse resulted a 75% decrease of mortality rate and better extended survival time following street rabies virus infection. Higher number of CD4 + T cells, TLR3 and TLR7 expression in the brain parenchyma observed in the groups receiving both combined agonist therapies at the levels of 25 μg and 50 μg. In spite of decreased number of neuronal cell, significant higher number of astrocytes was shown in the group given (Poly + Imi)25 μg. The obtained results also pointed to the dramatic decrease of HSP70 expression in all groups of infected mice whereas higher number of apoptotic cells and Caspase 8 expression were recorded in (Poly + Imi)25 μg treated group. Furthermore, the cytokine profile consisting the increased levels of TNF-α, IFN-γ and IL-4 revealed that both humoral and cellular responses were highly modulated in combination therapy of 50 μg of Imiquimod and Poly I:C. Reduced viral load as quantified by real-time PCR of rabies N gene expression in the brain also correlated with the better survival of agonist-treated groups of mice. Based on obtained results, we have presented evidences of beneficial utilization of combined agonist therapy composed of TLR3/TLR7 ligands. This treatment regimen extended survival of infected mice and decreased significantly their mortality rate. We believe that the results of synergy-inducing protection of both TLR3/TLR7 agonists lead to the enhancement of innate immune responses cells residing in the CNS which warrant the studies to further understanding of crosstalk mechanisms in cellular immunity against rabies in the future. Highlights: The immune responses through evaluation of cellular changes, Th1 and Th2 responses in the brain tissue were investigated Following treatment with combination of PolyI:C and Imiquimod agonists. Treatment with combination of PolyI:C and Imiquimod agonists resulted a 75% decrease of mortality rate and better extended survival time. The cytokine profile TNF-α, IFN-γ and IL-4 revealed highly modulation in combination therapy. Both combined agonist therapies resulted higher number of CD4 + T cells, TLR3 and TLR7 expression in the brain parenchyma. Higher number of apoptotic cells and Caspase 8 expression were recorded in the combined agonist therapies.